Investigation of shear band mechanism in reinforced soil retaining wall using pullout tests - İmamoğlu, Şevket. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
Geosynthetic Reinforced Soil in essence is the use of polymeric reinforcements into soil body to strengthen mechanical properties of the soil. Innovative applications of geosynthetic reinforced soil have signi cantly increased in last decades. Geosynthetic Reinforced Soil-Integrated Bridge System (GRS-IBS) is a new concept integrating roadway approaching slabs of the bridge and superstructure on geosynthetic reinforced soil. Design and construction guidelines are being adapted to recent innovative concepts. In order to propose a complete guideline, serviceability and failure mechanism should be thoroughly. Shear bands are localized shear deformations causing the failure of reinforced soil. In this research, pullout test is selected to observe shear band mechanism under di erent parameters. A modi ed small pullout test setup were developed which allows direct displacement measurements of the particles with image analysis, and were utilized to observe shear band mechanism. Digital Image Correlation technique has been utilized to determine displacement of soil particles. Tests were performed under di erent overburden pressure, average soil particle size and reinforcement geometry. The shear band mechanism observed with the modi ed setup and measurement technique is consistent with the literature, con rming the suitability of the applied testing method.
Keywords: Geosynthetics.; Reinforced soils.; Bridges -- Foundations and piers -- Design and construction.; polymeric reinforcements